The Role Of The International Disaster Management Agency In Efforts To Help Indonesia As A Disaster Prone Country - Erlina, Erlina .-; Sari, Nurlaila Aprilia; Lita, Lita Rosalina (Universitas Malayati, 2024)
Indonesia is one of the disaster-prone areas. Disaster-prone areas are areas that frequently or have a high potential for experiencing natural disasters. Apart from Indonesia, there are several countries that also occupy high positions in disaster-prone areas . These areas are the Philippines with a World Risk Index of 46.82 , and India with a World Risk Index of 42.31. Meanwhile, the World Risk Index for Indonesia is 41.46 . The purpose of this research is to determine the role of the International Disaster Management Agency in efforts to help Indonesia as a disaster-prone country. This research uses normative legal research methods or literature study . The results of this research show that the participation of international institutions and foreign non-governmental institutions is regulated in article 30 paragraphs 1-3 of Law no . 24 of 2007 and further clarified with the issuance of Government Regulation No. 23 of 2008 concerning government regulatory provisions regarding the role of international institutions and foreign non-governmental organizations in disaster management . Overall, the process of receiving international disaster aid involves coordination between governments, related institutions and international organizations. The process begins with an official statement of acceptance of the offer of assistance, continues with determining the type and amount of assistance needed, and finally the delivery and distribution of assistance to those in need. To manage international aid and to facilitate access to the International Disaster Management Agency, Indonesia through BNPB issued a Head of BNPB Regulation or what could be called Perka BNPB No. 22 of 2010 concerning the Role of International Organizations and Foreign Non-Governmental Organizations in Emergency Response